2021
DOI: 10.3390/v13071272
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus DNA Exacerbates Colitis Symptoms in a Mouse Model of Inflammatory Bowel Disease

Abstract: Infection with EBV has been associated with various inflammatory disorders including inflammatory bowel diseases (IBD). Contribution of this virus to intestinal disease processes has not been assessed. We previously detected that EBV DNA triggers proinflammatory responses via the activation of endosomal Toll-like receptor (TLR) signaling. Hence, to examine the colitogenic potential of EBV DNA, we used the dextran sodium sulfate (DSS) mouse colitis model. C57BL/6J mice received either DSS-containing or regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…The EBV DNA provokes pro-inflammatory responses via toll-like receptor (TLR) signaling (Salloum et al 2018 ). The EBV DNA can also enhance the expression of IFN-γ, IL-17A and TNF-α in the in vivo colitis model, exacerbating the colon damage (Wu et al 2019 ; Andari et al 2021 ) and leading to increase of disease severity (Kato et al 2021 ). T cells, B cells and NK cells infections also occur, impairing cellular immunity.…”
Section: Methodsmentioning
confidence: 99%
“…The EBV DNA provokes pro-inflammatory responses via toll-like receptor (TLR) signaling (Salloum et al 2018 ). The EBV DNA can also enhance the expression of IFN-γ, IL-17A and TNF-α in the in vivo colitis model, exacerbating the colon damage (Wu et al 2019 ; Andari et al 2021 ) and leading to increase of disease severity (Kato et al 2021 ). T cells, B cells and NK cells infections also occur, impairing cellular immunity.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it increases the severity of colon damage. These findings indicate that EBV DNA increases pro-inflammatory responses in colitis [42]. Study results showed that EBV infection increases the prevalence of lymphoproliferative disorders in IBD patients after using immunosuppressive drugs [43].…”
Section: Hpv Colonization Does Not Appear To Be Associated With Ibd D...mentioning
confidence: 67%
“…Likewise, recent studies formed the same conclusions in cohorts of Chinese patients with IBD (20)(21)(22)(23). In addition to these clinical studies, a recent study using an IBD mouse model, namely, the dextran sodium sulfate (DSS) mouse colitis model, detected that the presence of EBV DNA exacerbated colitis by aggravating colonic disease activity and increasing damage to the colon histologic architecture; this result indicates the possibility of potential therapeutic approaches targeting endosomal Toll-like receptor (TLR) signaling, which needs to be tested in large proportions of patients with IBD (27).…”
Section: The Influence Of Ebv Coinfection On the Clinical Course Of I...mentioning
confidence: 99%